OPTIMALISASI PEMUNGUTAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN DI KOTA TOMOHON - Moningka, Christy Virginia; Manossoh, Hendrik; Tangkuman, Steven J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
By the presence of regional autonomy, every region in Indonesia are required to do their own regional financing. Own Source Revenue is a source of regional financial and funding of the government. The Own Source Revenue consists of local taxes, levies, the result of the separated local asset management, and another Own Source Revenue that is valid. In relation to Own Source Revenue, The tax of Non-Metallic Minerals and Rocks is one type of the tax that need to be in government’s attention in Tomohon City. The purpose of this research is to know and understand optimization of non-metallic mineral and rock taxes in Tomohon City. The method used in this research is qualitative descriptive analysis. Data gained by field studies. The results of this research indicate that the management of Non-Metallic Mineral and Rock taxes in Tomohon City are still not optimal due to tax realization in 2013-2017 has not reached the target that has been determined. The management of Non-Metallic Mineral and Rock Taxes that has not been optimal is due to lack of the human resources for tax collection officers, facilities and infrastructure in the office is still inadequate, still lack of supervision from the officers, online information systems that has not been developed and lack of public awareness of the importance of paying taxes.Keywords : revenue, local taxes, non-metallic mineral and rock taxes, optimization